Dampak Implementasi Change Management pada Organisasi - Lianna Sugandi (Bina Nusantara University, 2013)
Changes have survival benefits for an organization. without any change, it can be ascertained that the age of the organization will not last long. Changes intend to make the organization not a static but remained dynamic in the face of changing times. A leader should have a vision and a change in the strategy based on assumptions about future conditions that are expected to occur. Only a leader who owns the personality, behavior, and the sense of power that is able to deal with change.